PATIENTS WITH NEUROLOGICAL DISEASES: RATIONALE FOR PHARMACOECONOMIC EVALUATION OF COST OPTIMIZATION FOR MANAGEMENT WITH NEURON-SPECIFIC PROTEINS ASSESSMENT AS MARKERS OF INCREASED BLOOD-BRAIN-BARRIER PERMEABILITY - D. V. Blinov (Фармакоэкономика, 2015)
becoming increasingly widespread evaluation of the blood-brain barrier (BBB) resistance to predict severity and outcome of epilepsy, stroke, traumatic brain injury (TBI) and other neurological disorders by assessment of neuron-specific proteins (NSP)  concentration in biological fluids. In this work possibility to predict the severity and outcome of perinatal hypoxic-ischemic lesion  of the central nervous system by this method were determined. It could be an example of a direct impact on the cost of treatment  and rehabilitation for patients with neurological disorders. Objective: to evaluate the dynamics of serum neuronspecific enolase  (NSE) and glial fibrillary acid protein (GFAP) concentration over a 6-month period of life in infants with cerebral ischemia. Materials and Methods. 49 infants with the perinatal hypoxic ischemic lesion of the CNS and gestational age between 32 and 41 weeks have been examined. 28 healthy term babies comprised the control group. For comparison patients were divided into the following groups: based on the 1-minute Apgar score: 1-3 scores (group А, 1-3), 4-6 scores (group А, 4-6) and 7-9 scores (group А, 7-9); based on their gestational age (GA): GA of 32-33 weeks, GA of 34-36 weeks and GA of 37-40 weeks; babies with the intra-ventricular hemorrhages (IVH group) and periventricular leukomalacia (PVL). Serum NSP levels were measured quantitatively using the enzyme immunoassay (EIA). Results. A significant increase of serum NSE and GFAP levels was found in groups А 1-3, А 4-6 and А 7-9 one week postpartum as compared to the control group. Over the whole observation period serum of both NSP concentration showed strong correlation with the severity of perinatal hypoxic-ischemic lesion of the CNS which was reflected in the Apgar score. Both during postpartum week one and further on the serum NSE levels were significantly higher in group GA 32-33 as compared to groups GA 34-36 and GA 37-41, as well as the control group. Starting from postpartum week one, serum NSE levels in the PVL group were significantly lower than in the IVH group. There was a delayed increase of serum GFAP levels at postpartum week 3 and NSE levels at postpartum week 4. Conclusion. The obtained results confirm the ongoing long-term abnormal BBB permeability for NSP after the perinatal hypoxic-ischemic lesion of the CNS which reflects the chronic course of a given pathology, that directly affects the cost of management for such patients. These changes are more pronounced in babies of lower gestational age. At the same time, publications of NSP IFA pharmacoeconomic evaluation and health technology assessment in management of patients with neurological diseases are not identified. evaluation is not identified with the evaluation of publications IFA NBF in neurological disorders in terms of pharmacoeconomics and health technology assessment. The results of this analysis the cost of diagnosis and treatment costs could be useful for the implementation of this method in the practice of the management of patients with neurological disorders. The results of such analysis could be useful for the implementation in the practice.